2016
DOI: 10.1080/10691898.2016.1158017
|View full text |Cite
|
Sign up to set email alerts
|

Flipping an Introductory Biostatistics Course: A Case Study of Student Attitudes and Confidence

Abstract: Flipped classrooms have become an interesting alternative to traditional lecture-based courses throughout the undergraduate curriculum. In this article, we compare a flipped classroom approach to the traditional lecture-based approach to teaching introductory biostatistics to first-year graduate students in public health. The traditional course was redesigned to include video lectures and online quizzes which the students were expected to complete before coming to class, followed by a short in-class lecture an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 17 publications
0
23
0
1
Order By: Relevance
“…Studies investigating students' attitudes toward statistics were mostly collected data from different disciplines other than engineering such as business, psychology, and health sciences (e.g., Carlson & Winquist, 2011, Chiesi & Primi, 2009Gundlach et al 2015;Griffith et al, 2012). These studies showed that using technology (Huynh, Buglin, & Bedford, 2014;Loux, Varner, & VanNatta, 2016) and use of real examples related to students' field or life (Kiekkas et al, 2015;Neumann, Hood, & Neumann, 2013); use of classroom workbooks (Carlson & Winquest, 2011), and use of alternative assessment methods (Posner, 2011) might help students to have more positive attitudes toward statistics. However, some studies showed that students' attitudes toward statistics generally declines throughout the semester (Schau & Emmioglu, 2012); even though, interventions have been made (Carnell, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies investigating students' attitudes toward statistics were mostly collected data from different disciplines other than engineering such as business, psychology, and health sciences (e.g., Carlson & Winquist, 2011, Chiesi & Primi, 2009Gundlach et al 2015;Griffith et al, 2012). These studies showed that using technology (Huynh, Buglin, & Bedford, 2014;Loux, Varner, & VanNatta, 2016) and use of real examples related to students' field or life (Kiekkas et al, 2015;Neumann, Hood, & Neumann, 2013); use of classroom workbooks (Carlson & Winquest, 2011), and use of alternative assessment methods (Posner, 2011) might help students to have more positive attitudes toward statistics. However, some studies showed that students' attitudes toward statistics generally declines throughout the semester (Schau & Emmioglu, 2012); even though, interventions have been made (Carnell, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of online and flipped formats has been reported in the literature in many different disciplines, such as computer programming and veterinary professional skills (Moffett and Mill 2014;Mok 2014). This trend is also apparent in the health sciences, including nursing, physiology, and epidemiology (Critz and Knight 2013;Tune 2013;Moraros et al 2015;Howard et al 2017), as well as in (bio)statistics (Keeler and Steinhorst 1995;Samsa et al 2012;Wilson 2013;Schwartz 2014;Winquist and Carlson 2014;Gundlach et al 2015;Peterson 2015;Loux et al 2016;McLaughlin and Kang 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Masterlevel public health students (commonly known as MPH students) constitute a sizable portion of consumers of today's biostatistics education. However, only recently did this distinct population of students become targets of focused pedagogical research by statistics educators (e.g., Loux et al 2016). This reflects an increasing awareness among statistics education researchers that students in different disciplines require different statistical curricula and accordingly different statistical pedagogical methods.…”
Section: Introductionmentioning
confidence: 99%
“…The following real-world example further underscores the need to fill the foregoing critical gap. The flipped classroom approach is increasingly popular among biostatistics educators (Loux et al 2016, McGraw and Chandler, 2015, McLaughlin and Kang 2017, Styers et al 2018). However, a study by Jensen et al (2015) suggests that the known benefits of the flipped classroom may not be attributable to the flipped classroom per se.…”
Section: Introductionmentioning
confidence: 99%